Characterization and discrimination of steroidal saponins in Tribulus terrestris L. and its three different aerial parts by chemical profiling with chemometrics analysis. Issue 22 (2nd November 2018) - Qi, Peng; Zheng, Yuanyuan; Shen, Yao; Wang, Jianwei; Bi, Qirui; Feng, Ruihong; Yang, Min; Hou, Jinjun; Wu, Wanying; Sun, Shenguo
Abstract: Tribulus terrestris L. is a well‐known medicinal plant from subtropical areas. In China Pharmacopoeia, only the fruit of T. terrestris is recorded to be the medicinal part. But some pharmaceutical preparations and food supplements made of total saponins of aerial part of T. terrestris including fruits, stems, and leaves are commercially available. However, steroidal saponins in different parts have not been studied extensively. So differentiating three parts and ensuring reasonable application of T. terrestris has been an important issue. Herein, we developed an integrated platform based on components profiling and chemometrics analysis to comparatively characterize and investigate steroidal saponins in three parts. As a result, a total of 84 steroidal saponins were characterized or tentatively identified, including 20 compounds reported for the first time. A clear separation of the three parts was achieved by partial least squares discriminant analysis based on the identified saponins, and 17 saponins were screened as biomarkers. Support vector machines model established based on 17 markers showed excellent predication accuracy of 100%. Finally, different distribution of steroidal saponins in three parts was shown obviously by heatmap visualization. These results provide promising perspectives for quality control of Chinese medicine, especially those with different medical parts.